Perancangan E-Book Food Rescue oleh Food Bank Bandung untuk Pengelola Industri Kuliner di Kota Bandung - Putri, Citra Kemala; Agnia Annisa Putri, Banon Gilang M.K.I, Diwan Setiawan, (SEIKO : Journal of Management & Business, 2024)
In the culinary industry, the problem of food waste accumulation is a serious concern because of its impact on the environment and economy. Much of the food produced by the culinary industry is still suitable for consumption (food surplus), but many of the culinary industries do not know information about the distribution of food surplus. Distributors of food surplus are commonly called food banks, which are spread all over the world. An active food bank in Bandung City is Food Bank Bandung (FBB), one of the ongoing programmes is Food Rescue, a programme to rescue food surplus and distribute it to people in need. Unfortunately, the existing information media is still less visually representative so it requires redesign. The urgency of this research is the need for redesigning information media using visual communication design principles to become an effective and efficient solution. Information media has great potential to become a bridge between target audiences and distributors to communicate the distribution flow of food surplus in the culinary industry. This research aims to (1) identify the types of information needed by the culinary industry in managing food surplus, (2) study the media preferences needed by the culinary industry in obtaining information related to Food Bank Bandung and the Food Rescue programme, (3) assess the effectiveness of existing information media in disseminating knowledge and practices of handling food surplus, (4) describe the implications of the findings for the development of more effective communication strategies in handling food surplus in the culinary industry. The method used in this research is a qualitative method that includes interviews, questionnaires, FGDs, and observations as supporting data. The results of this research produced the main information media in the form of e- books and several supporting media such as videos, social media content, and merchandising. Almost all media can be accessed online to facilitate the dissemination of information to culinary industry managers in Bandung. Keywords: food surplus, culinary, Food Bank, redesign, e-book